Use of GnRH and PGF for synchronized ovulation and fixed-time inseminations - Y. Kobayashi; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1994)
Holstein cows and virgin heifers were treated with GnRH and PGF in a novel 2a ovulation synchronization protocol, which involves one fixed-time insemination. One injection of GnRH is given on a Monday morning, followed in 7 days with an injection of PGF . Approximately 32 hr later, ovula- 2a tion is induced with a second injection of GnRH, and one insemination is made 18 hr later. Control cattle were given one injection of PGF and inseminated at estrus. Preg- 2a nancy rates measured between 28 and 35 days after insemination by ultrasonography were slightly, but not significantly, higher in controls (52.9%) than in the ovulation synchronization treatment (44.3%). This treatment may be particularly well suited to cows in which estrus is rarely observed, as well as for synchronizing first or repeat services.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; PGF; GnRH; Ovulation synchronization; Pregnancy rates